Analysis of Emotional Elements in Short Stories "This Is About Me" by Putu Ayub Through Character Education Perspective - Sena Junjunan; Ika Mustika (JLER (Journal of Language Education Research), 2023)
Emotions that are born when reading can change a person's character to be more rational because the basic concept of emotion is an overflow of feelings felt by someone when doing something, with the aim of analyzing the emotional elements of Putu Ayub's short stories and exploring the supporting factors of emotions that occur in real life reality. By using a qualitative approach as a scalpel in examining this literary work entitled about me, it is expected to be able to give birth to a more meaningful deepening of the emotions of the role. The result of this research is the content of character education values that are implemented in Putu Ayub's short story manuscript to produce education on emotional regulation and maturity mindset so that they can be wise in making decisions. Thus, this research is oriented towards the formation of a wise character in thinking, especially in the millennial generation who are still emotionally unstable.